DYNAMIC MODEL OF THE CASH WAQF SYSTEM: DEEP UNDERSTANDING OF THE INTERDEPENDENCE OF ECONOMIC,SOCIAL, AND SHARIA LAW FACTORS - Hidayatullah Hidayatullah; Muhammad Fadhan Adhani, Putri Nabella Galuh Randa, I Made Dwijayantara (ADISAM Publisher, 2024)
This research delved into the dynamic model of the Cash Waqf system, aiming to cultivate a profound understanding of the intricate interdependencies among economic, social, and Shariah legal factors. A meticulous analysis was conducted on generating, allocating, and investing funds within the Cash Waqf framework, focusing on financial instruments such as investment portfolios. The cyclical nature of economic variables impacting Cash Waqf's performance over time was scrutinized, emphasizing the system's adaptability to diverse economic and social contexts. Social dynamics were integral, prompting a comprehensive investigation into the beneficiaries of Cash Waqf initiatives and their community engagement. Social impact indicators, including advancements in education, healthcare, and poverty alleviation, played a pivotal role in shaping Cash Waqf's dynamics. The model successfully captured the reciprocal relationship between economic activities and their social consequences, enhancing its holistic representation of the Cash Waqf system. Shariah legal considerations were intricately integrated into the dynamic model, ensuring compliance throughout the lifecycle of Cash Waqf. The research acknowledged inherent feedback loops and nonlinearities, illustrating how changes in economic variables or social dynamics created interconnected consequences. The adaptive nature of the Cash Waqf system was highlighted, emphasizing its resilience to external shocks and regulatory changes.